2024
DOI: 10.37978/tijfs.v5i1.319
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of Gray Scale Ultrasonography Versus Color Doppler In Suspected Cases of Acute Appendicitis

Abstract: ABSTRACT: BACKGROUND: A common surgical emergency is acute appendicitis. Various diagnostic tools are available to diagnosis acute appendicitis. Radiological investigations play an important role in making accurate and early diagnosis and thus preventing morbidity associated with the disease. OBJECTIVE: To determine the diagnostic accuracy of gray scale ultrasonography versus color Doppler in suspected cases of acute appendicitis. MATERIALS AND METHODS: The study was carried in the department… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Additionally, it was reported that an ultrasound examination identified appendicitis in 88.3% of the children. Although the correlation between paediatric appendicitis score and PAS was not statistically significant, ultrasound detected appendicitis in all children with a PAS of seven or higher; therefore, the paediatric appendicitis score is a valuable diagnostic tool, particularly in settings with limited resources (10).…”
Section: Discussionmentioning
confidence: 81%
“…Additionally, it was reported that an ultrasound examination identified appendicitis in 88.3% of the children. Although the correlation between paediatric appendicitis score and PAS was not statistically significant, ultrasound detected appendicitis in all children with a PAS of seven or higher; therefore, the paediatric appendicitis score is a valuable diagnostic tool, particularly in settings with limited resources (10).…”
Section: Discussionmentioning
confidence: 81%